2001
DOI: 10.1074/jbc.m102579200
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Mimics of the Vesicular Stomatitis Virus G-protein Transmembrane Segment Drive Membrane Fusion in Vitro

Abstract: The efficiency of cell-cell fusion mediated by heterologously expressed vesicular stomatitis virus G-protein has previously been shown to be affected by mutating its transmembrane segment. Here, we show that a synthetic peptide modeled after this transmembrane segment drives liposome-liposome fusion. Addition of millimolar Ca 2؉ concentrations strongly potentiated the effect of the peptides suggesting that Ca 2؉ -mediated liposome aggregation supports the activity of the peptide. Peptide-driven fusion was supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 36 publications
(55 reference statements)
1
55
1
2
Order By: Relevance
“…In addition to length, TM domains may exert a sequencedependent effect by altering lipid packing or membrane curvature within the donor lipid bilayer as part of the fusion process (8,9,29,34,49). In the case of p10, the small volume of the glycine residues and free mobility around the glycineglycine bonds could facilitate additional mobility of the fatty acyl groups of adjacent lipids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to length, TM domains may exert a sequencedependent effect by altering lipid packing or membrane curvature within the donor lipid bilayer as part of the fusion process (8,9,29,34,49). In the case of p10, the small volume of the glycine residues and free mobility around the glycineglycine bonds could facilitate additional mobility of the fatty acyl groups of adjacent lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of the Hydrophobic Core Length of KALR on Fusogenicity-Previous studies showed that peptides corresponding to the TM domain of the vesicular stomatitis virus G protein and of SNARE induce in vitro membrane fusion (67)(68)(69). It was proposed that the fusogenicity of TM domains depends on structural flexibility (67)(68)(69).…”
Section: Effect Of the Hydrophobic Core Length Of Kalr On Insertion Intomentioning
confidence: 99%
“…It was proposed that the fusogenicity of TM domains depends on structural flexibility (67)(68)(69). The relationship between TM peptide fusogenicity and structural flexibility was further shown by using a TM model peptide with variable proportions of ␣-helix/␤-sheet-promoting residues (42).…”
Section: Effect Of the Hydrophobic Core Length Of Kalr On Insertion Intomentioning
confidence: 99%
“…Alternatively, conformational flexibility of SNARE TMDs may support fusion. In fact, liposomes fuse efficiently when just TMD peptides corresponding to synaptic SNAREs or viral fusion proteins were incorporated into the bilayer (24,60). Since sequence variants displaying more stable ␣-helical conformations in isotropic solution were less fusogenic, fusogenicity may depend on the conformational flexibility of the ␣-helical SNARE TMDs in the membrane.…”
Section: Vam3 Transmembrane Domain Directs Vacuole Fusionmentioning
confidence: 99%